Highly emissive organic solids with remarkably broad color tunability based on N,C-chelate, four-coordinate organoborons - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Thorat, Shridhar; Maity, Arunava; Kulkarni, Prasad P.; Gonnade, Rajesh G.; Munshi, Parthapratim; Patil, Nitin T. (Chemical Communications, 2015)
Molecular fluorophores based on N,C-chelate, four-coordinate organo-borons exhibit tunable solid-state emission colors that cover the whole visible region from blue to red. The emission color can be tuned through the substituents on either quinolines or the boron center.